The influence of granulated peat on fattening qualities of pigs - Loeffler, T F; Tsybulkin, D V; Sundeev, P V (Mongolian Journal of Agricultural Sciences, 2018)
The article presents data of chemical composition of granulated peat "kozelkova" field. It is shown that the introduction in the diet of peat (to 10%) has a positive effect on growth rate of fattening of young pigs.